STUDI PEMAHAMAN BUKTI DAN PEMBUKTIAN DALAM GEOMETRI EUCLID MAHASISWA JURUSAN TADRIS MATEMATIKA IAIN TULUNGAGUNG - Beni Asyhar (Jurnal Pendidikan Matematika (JPM), 2015)
One of the problems to be solved in mathematics is a proof. At the college level, proving to be more important than the previous levels. When someone has a hunch about something (theorem), one of the most appropriate way to ensure that something (theorem) is true is by proving mathematically valid (formally). That is, the truth of the theorem is based on logical statements. However, proof of this is a problem when introduced during the learning. Not only the beginning students, final year students, moreover those already graduated are still experiencing difficulties in proving. This study attempts to describe the understanding of the concept of proof in mathematics and describes the ability of students in validating and compiling of proof in mathematics, particularly in Euclidean geometry using qualitative research approach, the type of case studies.